Water-rich incipient melt of the deep upper mantle indicates locally preserved low-velocity zones above the 410 km discontinuity - Longjian Xie; Tomoo Katsura; Nobuyoshi Miyajima; Tongzhang Qu; Ho-kwang Mao (Proceedings of the National Academy of Sciences, 2025)
Seismic low-velocity layers (LVLs), frequently attributed to hydrous-silicate melts, are detected globally but exhibit lateral discontinuities. Geophysical and laboratory studies of water content in the mantle transition zone (MTZ) and upper mantle solubility limits suggest these layers likely form through global dehydration melting near the 410 km discontinuity (D410). A key hypothesis posits that melts form globally but are preserved only where melt stability permits retention. However, challenges in quenching melts into glass or fine-grained crystals at mantle pressures have precluded precise determination of melt composition, fueling debates over the mechanisms governing LVLs’ sporadic distribution. Here, we developed a fast-quenching high-pressure cell assembly to synthesize hydrous glasses or fine-grained quench crystals at pressures >10 GPa, enabling high-precision analysis of incipient melt composition. Experiments at 13 GPa reveal that the 410 melt contains 43 mol% H 2 O, 9.2 mol% CaO, 30.5 mol% (Mg, Fe)O, 0.2 mol% Al 2 O 3 , and 17 mol% SiO 2 . The melt’s high water content necessitates Fe enrichment to achieve neutral buoyancy, which can only be sourced from Fe-rich heterogeneities (Fe # = 100Fe/(Mg+Fe) in mole; Fe # >18) within the MTZ. In contrast, melts derived from normal MTZ material (Fe # <18) remain buoyant and migrate upward, precluding stable layer formation. We conclude that global dehydration melting generates hydrous melts, but only Fe-rich heterogeneities enable melt retention, reconciling the coexistence of widespread LVL detections and their lateral discontinuities.